Sure bets or risky gambles? Understanding popular support for post-conflict constitutions - Kyle, Jordan; Resnick, Danielle (2023)
What shapes mass attitudes towards constitutional reforms in post-conflict contexts? Constitutional reform has long been a priority for states emerging from conflict, where there is a need to rectify the marginalization of certain groups, define the scopes of authority of different institutions, and delineate power-sharing arrangements. Yet, because constitutional reforms are often led by political elites, we typically lack insights into the views of the broader populace.